Altered Metabolic Flux due to Deletion of odhA causes l-Glutamate Overproduction in Corynebacterium glutamicum - Asakura, Yoko (American Society for Microbiology, 2007)
l-Glutamate overproduction in Corynebacterium glutamicum, a biotin auxotroph, is induced by biotin limitation or by treatment with certain fatty acid ester surfactants or with penicillin. We have analyzed the relationship between the inductions, 2-oxoglutarate dehydrogenase complex (ODHC) activity, and l-glutamate production. Here we show that a strain deleted for odhA and completely lacking ODHC activity produces l-glutamate as efficiently as the induced wild type (27.8 mmol/g [dry weight] of cells for the ohdA deletion strain compared with only 1.0 mmol/g [dry weight] of cells for the uninduced wild type). This level of production is achieved without any induction or alteration in the fatty acid composition of the cells, showing that l-glutamate overproduction can be caused by the change in metabolic flux alone. Interestingly, the l-glutamate productivity of the odhA-deleted strain is increased about 10% by each of the l-glutamate-producing inductions, showing that the change in metabolic flux resulting from the odhA deletion and the inductions have additive effects on l-glutamate overproduction. Tween 40 was indicated to induce drastic metabolic change leading to l-glutamate overproduction in the odhA-deleted strain. Furthermore, optimizing the metabolic flux from 2-oxoglutarate to l-glutamate by tuning glutamate dehydrogenase activity increased the l-glutamate production of the odhA-deleted strain.